Sosialisasi Belajar Memimpin dan Bertanggung Jawab Sejak Dini - Fatolosa Hulu; Sukurman Hia; Fitri Anita Lase; Enggie Novita Zai; Maximus Sohahau Laia; Mesrawati Hulu; Rainel Fitriana Laoli; Mordekhai Zebua; Putra Percaya Laia; Yamolala Zega (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity aims to provide socialization about the importance of learning to lead and be responsible from an early age to fifth-grade elementary school students. The socialization was carried out at Sihare'o Public Elementary School in West Gunungsitoli City using interactive lecture methods, group discussions, and role-play simulations designed to instill the values of leadership and responsibility in a fun way. The implementation results showed high student enthusiasm in participating in each session, as well as an increased understanding of the meaning of leadership, cooperation, and responsibility for tasks and groups. In addition, teachers appreciated this activity because it was considered to help support character learning in schools. This activity is expected to be the first step in building students' personalities who are confident, disciplined, and have a sense of responsibility, which ultimately will support the creation of a young generation with good character